Financial Literacy on Financial Well-Being: Roles of Financial Behavior and Skills in Consumer Mental Budgeting in Indonesia - Mandagie, Wenny Candra; Priyanto, Panji (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2026)
This study explores the complex relationships between financial literacy, financial behavior, other financial skills, and financial well-being, focusing on consumer mental budgeting in Indonesia. This study uses path analysis to examine how financial literacy is a foundational element that enhances financial behavior and other financial skills, ultimately contributing to improved financial well-being. This research uses structural equation modeling to estimate the relationship among the variables. This research surveyed the 15-58 age group in several urban areas of Java Island. The survey collected information on the indicators that constructed the latent variables. The results indicate that DFL is influenced by social-economic standing. The findings of this study reveal a strong positive correlation between financial literacy and financial behavior (path coefficient = 0.804), indicating that individuals with higher financial literacy are more likely to engage in effective budgeting practices. This study highlights the significant impact of financial behavior on financial well-being (path coefficient = 0.613), indicating that sound financial management is directly correlated with increased financial security and satisfaction. Although the relationship between other financial skills and financial well-being is positive (path coefficient = 0.219), the relationship is less pronounced than the direct effects of financial literacy and financial behavior. The results of this study underscore the importance of financial literacy as a catalyst for fostering positive financial behavior and improving overall financial well-being. This study contributes to the understanding of consumer mental budgeting. It offers valuable insights for policymakers and financial educators aiming to improve financial literacy and behavior among consumers in Indonesia.